The interplay between Azospirillum brasilense and the native bacterial communities in the soil and rhizosphere of maize (Zea mays L.) - Pedrinho, Alexandre; Mendes, Lucas William; do Rêgo Barros, Felipe Martins; Bossolani, João William [UNESP]; Kühn, Tayná Negri; Quecine, Maria Carolina; Andreote, Fernando Dini (Elsevier, 2024)
Azospirillum brasilense is a plant-growth promoting bacteria used as a bioinoculant in agriculture. However, the capacity of A. brasilense to establish itself in the soil and rhizosphere of different plants, as well as its interactions with the native soil bacterial community, are not fully understood. This knowledge gap can be attributed to inconsistencies in the quantity of the inoculant delivered (population size) and abiotic and biotic factors that modulate its performance. In this study, our objective was to gain a better understanding of how different-sized populations (sub-dose, recommended dose, and super-dose) of A. brasilense affect and interact with the structure, diversity, and connections of the native bacterial community in both bulk soil and rhizosphere of maize plants at different growth stages. Furthermore, we aimed to assess the effectiveness of these different-sized populations of A. brasilense in promoting plant growth. The introduction of a large population (recommended dose and super-dose) of A. brasilense significantly improved maize growth parameters, while a small population (sub-dose) did not. In the bulk soil, we observed that a large population of A. brasilense was capable of initially disrupt the native soil bacterial community. However, the native soil bacterial community was able to recover from the momentary disturbance and return to its initial state. In the rhizosphere of maize plants, large populations of A. brasilense extended their impact on the native bacterial community, possibly due to permanent changes in plant traits, such as root morphology and exudation. Furthermore, the co-occurrence network analysis revealed shifts in keystone taxa (i.e., taxa that confer high connectivity) in the rhizosphere of maize plants. A. brasilense played a key role at the early stages, but it was later replaced by Rhizobiales, a native soil bacterium. This study presents novel evidence of how different-sized populations of A. brasilense can influence microbe-microbe and plant-microbe interactions, ultimately affecting maize growth.
Keywords: Amplicon sequencing; Microbial ecology; Microbial interaction; Microbial invasion; Plant growth-promoting bacteria (PGPB)